Transcultural validation of the return-to-work self-efficacy scale in Korean patients with work-related injuries - Jeong-Eun Lee; Su Bin Yoo; Ja-Ho Leigh (BMC, 2020)
Abstract Background This study aimed to develop a Korean version of the Return-to-Work Self-Efficacy (RTWSE)-19 Scale using forward- and backward-translation and investigate the validity of the RTWSE Scale specifically for Korean workers with work-related injuries. Methods Participants were 202 injured workers who had filed a claim accepted by the workers' compensation system and had received medical rehabilitation at workers' compensation hospitals following a work-related musculoskeletal injury. Among these participants, 88.1% were male, 54.5% were over 45 years, 45.5% were manufacturing employees, and 54.5% were craft or machine operator and assemblers. The 19 item RTWSE-19 scale was developed by Shaw et al. and have three underlying subscales: (i) meeting job demands, (ii) modifying job tasks, and (iii) communicating needs to others. Statistical analysis included exploratory factor analysis (maximum likelihood estimation with oblique quartimin rotation), internal consistency reliability using Cronbach's alpha, and correlations with related measures: pain intensity; fear-avoidance beliefs; general health; depression; and general self-efficacy. Results Using exploratory factor analysis, three factors with 17 items were identified: meeting job demands, modifying job tasks, and communicating needs to others. The removal of two items in the modifying job tasks domain resulted in an increased reliability. The Korean version of the RTWSE-17 showed reasonable model fit (CFI = .963; TLI = .943; RMSEA = .068; SRMR = 0.029), satisfactory reliability (r = 0.925), no floor and ceiling effect, and construct validity. Conclusions The Korean RTWSE-17 scale was found to possess good psychometric properties and could address different injury types ranging from fractures to amputations involved in sub-acute and rehabilitation phases in the Korean context. This study's findings provide insights for practitioners and researchers to return to work after rehabilitation in a Korean clinical and workplace setting.